Social Inequality as an Obstacle to Public Legal Compliance - Novita Widia Sari; Dinda Dinanti (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
One of the main obstacles to achieving stable legal compliance in Indonesia is social inequality. This study aims to explain how social disparities affect the implementation of law and how injustice shapes the public’s legal perceptions and behaviors. The findings show that law enforcement in Indonesia remains selective: strict toward vulnerable groups but lenient toward influential ones. This conclusion is drawn through a literature study employing a descriptive-analytical approach. Based on the theories of Weber and Foucault, the analysis reveals that law functions not only as a set of rules but also as an instrument of power that enables the reproduction of social inequality. Consequently, the legitimacy of the law weakens, and society begins to adopt an instrumental pattern of compliance. This study emphasizes that law enforcement requires structural reforms, including institutional transparency, improved access to legal aid, and policies that better support vulnerable groups so that the law can operate fairly and efficiently.